2008
DOI: 10.1248/cpb.56.82
|View full text |Cite
|
Sign up to set email alerts
|

A New Labdane Diterpene from the Flowers of Solidago canadensis

Abstract: Solidago canadensis L. is an Asteraceae widely distributed across North America, occurring in almost every state of the U.S.A. and throughout Canada. Numerous interesting secondary metabolites such as: flavonoids, phenolic acids and glucosides, polysaccharides, diterpenes, triterpenoid saponosides, tannins and essential oils 1) were reported for the genus Solidago. Previous phytochemical studies of S. canadensis have led to the isolation of flavonoids, 2,3) phenolic acids, 4) sesquiterpenes, 5) diterpenes 6,7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…At 363.18131 (C 20 H 27 O 6 ) and at 347.18640 (C 20 H 27 O 5 ) diterpenes with DBE of 7 can be solidagenone derivatives with oxidized furan ring. Bradette‐Hébert et al () isolated from Solidago canadensis the diterpene solicanolide with M = C 20 H 28 O 6 . Solicanolide‐type diterpenes with ethyl ether as side chains (M = C 24 H 40 O 7 and C 24 H 38 O 6 ) are also detected, because 10 hydrogens and one oxygen (CH 3 CH 2 O) were probably added to C 20 H 28 O 5 and C 20 H 28 O 6 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…At 363.18131 (C 20 H 27 O 6 ) and at 347.18640 (C 20 H 27 O 5 ) diterpenes with DBE of 7 can be solidagenone derivatives with oxidized furan ring. Bradette‐Hébert et al () isolated from Solidago canadensis the diterpene solicanolide with M = C 20 H 28 O 6 . Solicanolide‐type diterpenes with ethyl ether as side chains (M = C 24 H 40 O 7 and C 24 H 38 O 6 ) are also detected, because 10 hydrogens and one oxygen (CH 3 CH 2 O) were probably added to C 20 H 28 O 5 and C 20 H 28 O 6 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of 3,4,5-tri-O-caffeoylquinic acid (3) in Solidago species. 3,5-Di-O-caffeoylquinic acid (1) was previously isolated from S. virgaurea (Thiem et al 2001;Choi et al 2004), while 3,4-di-O-caffeoylquinic acid (2) and 4,5-di-O-caffeoylquinic acid (4) were previously reported in other Solidago species (Bradette-Hebert et al 2008). …”
Section: Hplc Chromatographic Profiling and Isolation Of Major Compoundsmentioning
confidence: 91%
“…Other authors reported the presence of sesquiterpenes, labdane diterpenes, saponins, chlorogenic acid and caffeic acid in Solidago species (Bader et al, 1995;Apati et al, 2002;Bradette-Hébert et al, 2008;Steliopoulos et al, 2008).…”
Section: Introductionmentioning
confidence: 95%